Considerações sobre a definição de Epicórtex - Barbosa, Suzana Bissacot [UNESP]; Marcelli, Marcelo Pinto (My University, 2010)
The species of the family Parmeliaceae can be divided into two major groups according to the presence of pseudocyphellae or pored epicortex. In the first group of species the upper cortex is composed by exposed hyphae and on the second group is characterized by hyphae covered by a thin epicortex layer composed of polysaccharides. The presence and type of epicortex is considered a constant character in level of genus and section, and useful in the taxonomy of the family. However through studies by different authors, in light microscopy and scanning electron microscopy added to the chemical analysis, the concepts of epicortex have changed over the time, according to opinions of experts in the area and these concepts are presented and discussed here.

As espécies da família Parmeliaceae podem ser divididas em dois grandes grupos de acordo com a presença de pseudocifelas ou epicórtex poroso. No primeiro grupo de espécies o córtex superior é consistiuído de hifas expostas e no segundo grupo é caracterizado por hifas cobertas por um fino epicórtex constituído por polissacarídeos. A presença e o tipo de epicórtex é considerado um caráter constante ao nível de gênero e de seção e útil na taxonomia da família. No entanto através da realização de estudos, por diferentes autores, em microscopia de luz e microscopia eletrônica de varredura adicionados à análises químicas, os conceitos de epicórtex foram mudando ao longo do tempo, de acordo com as opiniões dos especialistas na área e esses conceitos são aqui apresentados e discutidos.
Considerations on the definition of Epicortex
Keywords: Epicortex; Parmeliaceae; Pseudocifelas